Localizing Land Governance, Strengthening the State: Decentralization and Land Tenure Security in Uganda. (17th November 2015) - van Leeuwen, Mathijs
Abstract: Decentralization of land governance is expected to significantly improve land tenure security of small‐scale farmers in Africa, through ensuring better protection of their assets and reducing land‐related conflicts. This paper, however, cautions not to have too high expectations of transferring responsibilities for land administration and dispute resolution to local government bodies. Field research in Mbarara District in south‐western Uganda brings out how decentralization has limited impacts in terms of localizing land services provision. Nonetheless, local land governance has transformed in important ways, as decentralization adds to institutional multiplicity, and fuels competition among state and non‐state authorities, and about the rules they apply. Rather than strengthening local mechanisms for securing tenure, the reforms introduce new forms of tenure insecurity, fail to transform local conventions of dealing with land disputes and delegitimize local mechanisms for securing tenure. In practice, decentralization has had limited effects in securing tenure for the rural poor, yet reinforces the presence of the state at the local level in diverse ways.